2004
DOI: 10.1002/pmic.200400981
|View full text |Cite
|
Sign up to set email alerts
|

Effects of benzo(a)pyrene on protein expression in Jurkat T‐cells

Abstract: Polycyclic aromatic hydrocarbons (PAHs) are ubiquitous environmental pollutants of air, water and soil, and are produced by the incomplete combustion of organic materials. The International Agency for Research on Cancer has characterized PAHs as carcinogens. In this study, we investigated the effects of benzo(a)pyrene (B(a)P), which is the most carcinogenic member of the PAHs, on Jurkat cell protein by proteomic analysis. Jurkat cells were treated with various concentrations of B(a)P (0, 2.5, 5, 10, 20 or 40 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 46 publications
0
40
1
Order By: Relevance
“…Plasma samples were prepared for 2-DE analysis as described previously (Oh et al, 2004). Lipids and salts were removed from samples using a molecular weight cut off column (3 kDa; Amicon, Millipore).…”
Section: -De Page Sample Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…Plasma samples were prepared for 2-DE analysis as described previously (Oh et al, 2004). Lipids and salts were removed from samples using a molecular weight cut off column (3 kDa; Amicon, Millipore).…”
Section: -De Page Sample Preparationmentioning
confidence: 99%
“…This reactive metabolite exerts mutagenic and carcinogenic effects by reacting with DNA to form miscoding adducts, leading to the initiation of carcinogenesis (Conklin, 2000;Gelboin, 1980;Hicks, 1983). Previously, we reported that BaP down-regulates the expression of breast cancer metastasis-suppressor 1, differentiation-related gene (Drg1, a putative tumor suppressor) and a putative lung tumor suppressor in Jurkat cells (Oh et al, 2004). Furthermore, the increased DNA damage induced by BaP has been associated with the activation of p53 tumor suppressor and induction of programmed cell death (Umannova et al, 2008).…”
Section: Introductionmentioning
confidence: 97%
“…Following BaP exposure, some cells significantly downregulate proteins that are involved in metastasis and tumor suppression . For example, one study found that downregulated proteins were involved with apoptosis, cell structure, metabolism, and DNA synthesis . Proteins involved with cell proliferation, growth, and differentiation were also upregulated .…”
Section: Discussionmentioning
confidence: 99%
“…A decrease in proteins associated with DNA synthesis was also found by Oh et al . [44] investigating benzo(a)pyrene [B(a)P], a polycyclic aromatic hydrocarbon which is a ubiquitous pollutant and carcinogen. Two concentrations of B(a)P, one cytotoxic, were used to investigate the potential for detection of biomarkers of diseases associated with B(a)P. Proteins associated with apoptosis and tumour suppression were found to be up‐regulated and those associated with energy metabolism, DNA synthesis and cell structure were down‐regulated.…”
Section: Alteration In Protein Production Following T Cell Activationmentioning
confidence: 99%